Neighborhood disorder and depressive symptoms in Jamaican adults: the mediating roles of neighborhood crime and safety problems and collective efficacy - Cunningham-Myrie, C.; Moore, T.; Wiggan, J.; Younger-Coleman, N.; McFarlane, S.; Gordon-Strachan, G.; Francis, D.; Bennett, N.; Govia, I.; Tulloch-Reid, M.; Ferguson, T. S.; Aiken, W.; et al. (Frontiers in Epidemiology, 2025)
BackgroundNeighborhood disorder has been found to be associated with worse mental health outcomes, such as depression. This study examined the association between perceived neighborhood disorder on depressive symptoms in a nationally representative sample of Jamaican adults, and whether any association was mediated by perception of neighbourhood crime and safety problems or collective efficacy (CE).MethodsSecondary analysis was conducted on the Jamaica Health and Lifestyle Survey (JHLS III). The JHLS III, a cross-sectional nationally representative survey, was administered to 2,807 individuals aged 15 years and older in Jamaica and completed in 2017. Regression analyses were performed to identify associations between perceived neighborhood disorder and depressive symptoms and mediation analyses to examine the roles of perceived neighborhood crime and safety problems and CE in the pathway between perceived neighbourhood disorder and depressive symptomatology.ResultsThe odds of depressive symptomatology were 1.55 (95% CI = 1.14, 2.10) times as high among respondents living in neighborhoods perceived as having high disorder compared to those with low disorder. Partial mediation by perceived neighborhood crime and safety problems and low CE in the disorder-depressive symptomatology relation was observed. Twelve percent and 7% of the association between neighbourhood disorder and depressive symptoms were explained through perceived neighborhood crime and safety problems and low CE, respectively. In serial mediation analysis the association between perceived neighborhood disorder and depressive symptoms was mediated by perception of neighborhood crime and safety problems which, in turn, was mediated by reported CE.DiscussionThe pathway between neighborhood disorder and depressive symptoms may be reduced by intervening on reducing neighborhood crime and safety problems and/or improving CE in Jamaican neighborhoods.